Cooling‐Triggered Shapeshifting Hydrogels with Multi‐Shape Memory Performance. Issue 26 (14th May 2018) - Hu, Xiaobo; Zhang, Daixuan; Sheiko, Sergei S.
Abstract: Heating‐triggered shape actuation is vital for biomedical applications. The likely overheating and subsequent damage of surrounding tissue, however, severely limit its utilization in vivo. Herein, cooling‐triggered shapeshifting is achieved by designing dual‐network hydrogels that integrate a permanent network for elastic energy storage and a reversible network of hydrophobic crosslinks for "freezing" temporary shapes when heated. Upon cooling to 10 °C, the hydrophobic interactions weaken and allow recovery of the original shape, and thus programmable shape alterations. Further, multiple temporary shapes can be encoded independently at either different temperatures or different times during the isothermal network formation. The ability of these hydrogels to shapeshift at benign conditions may revolutionize biomedical implants and soft robotics. Abstract : Cooling‐triggered shapeshifting hydrogels are designed by employing dual networks built by covalent and hydrophobic crosslinks. A temporary shape is fixed under heating by forming a hydrophobic network, and the original shape is recovered upon cooling by weakening the hydrophobic interactions. Further, the hydrogels exhibit a multi‐shape‐memory effect by isothermally programming different shapes at different temperatures or times.